Sustainable Tourism Development Combining Health And Culture As A Local Community-Based Wellness Tourism Attraction In Gebong Memarong Tradisional Village, Airabik, Bangka Regency - Hardyanti; Anggara, Bagas (Politeknik Negeri Bandung, 2025)
Gebong Memarong Airabik Traditional Village possesses significant potential for development as a health tourism destination, leveraging its rich natural resources, cultural heritage, and traditional healing practices. This study aims to identify the village's health tourism appeal and examine the roles of key stakeholders, including the Bangka Regency Tourism Office, the Indonesian Tourism Actors Association (ASPI), PT Timah Tbk, local tourism awareness groups (Pokdarwis), and indigenous communities. A qualitative approach was used, with data collected through direct observation, interviews, and documentation analysis. Findings indicate that collaboration between stakeholders and the local community has played a critical role in promoting the village and improving local human resource capacity. The development of health tourism is centered on the use of herbal plants for traditional medicine, which aligns with the principles of sustainable tourism. However, regulatory challenges—particularly concerning land use zoning—remain a threat to the preservation of local wisdom and sustainable development. Ongoing efforts are addressing these issues through formal regulation and the promotion of herbal products and wellness services, such as scrubs, herbal drinks, retreats, and spas for both domestic and international markets. This study emphasizes the importance of integrating cultural values and traditional knowledge into tourism planning, while ensuring institutional support and policy alignment for long-term sustainability.